Analisis Manajemen Persediaan pada UMKM Salon Desta di Kabupaten Lamongan - Nahning Intan Srirahayu; Masfufah Widya R; Mohd. Izazwan; Ach Syauqi Zulfian F (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the inventory management system of raw materials at Salon Desta MSME located in Lamongan, East Java. The method used is a qualitative case study with data collection techniques including in-depth interviews, direct observation, and documentation. The results show that Salon Desta has implemented basic management functions informally, but its inventory control aspect still relies on visual intuition without stock cards. Key challenges include the risk of stockout during peak demand and overstock of treatment products vulnerable to expiration. Recommendations include the integration of digital-based automated stock tracking features, determining reorder points, and regular management training.